Morbidity and mortality in patients with rheumatoid arthritis compared with an age- and sex-matched control population: A nationwide register study. (30th May 2019) - Løppenthin, Katrine; Esbensen, Bente Appel; Østergaard, Mikkel; Ibsen, Rikke; Kjellberg, Jakob; Jennum, Poul
Objective: The aim of this study was to examine the prevalence of morbidity and mortality in patients with seropositive rheumatoid arthritis (RA). Methods: Data were obtained from national population-based registries in the period 1998–2009. Prior to the seropositive RA diagnosis (International Classification of Disorders 10th revision M05), we identified a total of 21, 558 patients and 87, 384 age- and sex-matched control subjects. Odds for morbidity were calculated before and after the RA diagnosis. We estimated the overall survival based on the Kaplan–Meier method. Results: Patients with RA had statistically significantly higher odds for a number of co-morbidities prior to the onset of RA including diseases of the musculoskeletal system (odds ratio (OR) 3.10, 95% confidence interval (CI) 3.00–3.21), diseases involving the immune system (OR 1.45, 95% CI 1.29–1.64), endocrine diseases (OR 1.09, 95% CI 1.01–1.17), diseases of the circulatory system (OR 1.08, 95% CI 1.03–1.14) and diseases of the respiratory system (OR 1.30, 95% CI 1.22–1.38), compared with age- and sex-matched control subjects. After the RA diagnosis, the same trend was seen with higher odds for the same co-morbidities. We found a 5-year survival of 80% (95% CI 78–81%) for patients with RA, while for control subjects it was 88% (95% CI 88–89%). Conclusion: Compared with age- and sex-matched controls, patients with seropositive RA have higher odds for several co-morbidities prior to and, particularly, after the diagnosis of RA. Furthermore, patients with RA have a lower overall survival compared with age- and sex-matched controls.